Perlantikan, perlucutan dan etika hakim syarie di Malaysia - Jasri Jamal ,; Khairuddin Mohd Amin, (Fakulti Undang - Undang, 2002)

(untitled)
Islamic judicial system has laid down several requirement that must be fulfilled by Qadis or Shari’ah judges. It is clear that the Shari’ah judges is responsible to uphold the justice, which is to be followed and enforced on cases that has been decided earlier by them (judge). Therefore, it is important for the qadi/judge to safeguard his conducts and attitudes from anything that many cast doubt over his fairness in sentencing Jabatan Kehakiman Syariah Malaysia (JKSM) issued a directive for the application of code of ethics for the Syari’ah judges (adab al-qadi). However, the appointment and resignation of them are still under the state jurisdiction through its Administration Of Islamic Law Enactment and Syariah Courts Enactment